Impact Analysis of Large-Scale Wind Farms Integration into Weak Transmission Grid from the Viewpoint of Power Quality Issues, Wake Effect, Seasonal Variations and VAR Compensation - Shah Rukh Abbas (00000273416); Dr Syed Ali Abbas Kazmi (USPCAS-E NUST, Islamabad, 2020)
TH-228
Keywords: MS-EEP Thesis MS Thesis